Role of CT and MR enterography in the evaluation of inflammatory bowel disease - Mishra, Supriya Sundar; Shahi, Anamika; Rath, Mahesh (International Journal of Research in Medical Sciences, 2025)
Background: Inflammatory bowel disease (IBD) requires accurate diagnosis and assessment of disease activity for effective management. CT Enterography (CTE) and MR Enterography (MRE) are key imaging modalities for evaluating small bowel involvement in IBD. This study compares their diagnostic performance in detecting IBD, assessing disease activity, and identifying complications. Methods: A prospective observational study was conducted on 48 patients with suspected or confirmed IBD. All patients underwent both CTE and MRE, followed by ileo-colonoscopy within two weeks to maintain consistency in disease status. Endoscopy served as the reference standard. Sensitivity, specificity and accuracy were calculated for each modality, with statistical analysis performed using IBM SPSS version 29.0. Interobserver agreement was evaluated using Cohen’s kappa coefficient (κ). Results: For diagnosing IBD, MRE showed a sensitivity of 86.6%, specificity of 92.7%, and accuracy of 89.65% (κ=0.73), while CTE demonstrated a sensitivity of 87.1%, specificity of 90.6%, and accuracy of 88.85% (κ=0.79). In detecting active disease, MRE achieved 84.5% sensitivity and 94.2% specificity (accuracy 89.35%, κ=0.76), whereas CTE showed 88.9% sensitivity and 83.7% specificity (accuracy 86.30%, κ=0.84). For chronic disease, MRE had 87.5% sensitivity and 91.2% specificity (accuracy 89.82%, κ=0.72), while CTE reported 88.3% sensitivity and 87.9% specificity (accuracy 88.10%, κ=0.77). Conclusion: Both CTE and MRE provide high diagnostic accuracy for IBD. MRE is preferred in younger patients due to the absence of radiation, while CTE remains useful for rapid evaluation in acute or elderly cases.